Lactic Acid Bacteria against Listeria monocytogenes - Bogea, Juliana Sousa; Manto, Luciane; dos Santos, Jucilene Sena; dos Santos, Lara Franco; Gotardo, Franciele Maria; Rodrigues, Laura Beatriz; dos Santos, Luciana Ruschel (Acta Scientiae Veterinariae, 2021)
Background: Listeria monocytogenes is a pathogenic bacterium that can contaminate food and cause public health problems due its ability to form biofilms and resistance to sanitizers, it is responsible for sanitary and economic losses in food producing establishments. The difficulties in controlling biofilms and increasing resistance to traditional antibacterial agents is motivating studies of alternative potential biological agents for the control of pathogenic biofilms, among which lactic acid bacteria (LABs) are included. The objective of this work was to evaluate the activity of LABs against Listeria monocytogenes biofilm formation on polystyrene plates, a surface commonly used in the food industry. Materials, Methods & Results: Lyophilized commercial strains of Bifidobacterium animalis, Lactobacillus fermentum, Lactobacillus plantarum, Lactobacillus salivaris and Lactobacillus acidophilus were used. The strain of Listeria monocytogenes (L4) was isolated from polystyrene mats from a poultry slaughterhouse cutting room and demonstrated the ability to attach to microplates and resistance to sanitizers (sodium hypochlorite and hydrogen peroxide) at all times, temperatures and tested surfaces. The antimicrobial activity of LABs was evaluated by the agar diffusion method. The LABs that presented action on Listeria monocytogenes were selected for the inhibition and/or removal of biofilms in microplates, and all experiments were carried out in triplicate. Only Bifidobacterium animalis and Lactobacillus plantarum demonstrated action against Listeria. monocytogenes in the agar diffusion assays and were selected for inhibition and competition assays. Furthermore, competition of LABs against Listeria monocytogenes adhesion was evaluated. There was no significant difference between LABs and Listeria monocytogenes, alone or in combination, at temperatures of 30ºC and 37ºC in the Listeria monocytogenes inhibition assays on polystyrene surface. The lactic acid bacteria evaluated did not demonstrate inhibition of Listeria monocytogenes adhesin testes with optical density visualization, however, it was possible to identify a reduction in Listeria monocytogenes counts with the application of Bifidobacterium animals and Lactobacillus plantarum in the testes of competition against biofilm formation. In competition tests Bifidobacterium animalis and Lactobacillus plantarum have an injunction in Listeria monocytogenes, indicating that these lactic acid bacteria can retard Listeria biofilm formation on polystyrene surfaces and thus help control the pathogen in the food industry. Discussion: A potential mechanism to control biofilm adhesion and formation of pathogens for nutrients and fixation on surfaces, multiplication factors and surfaces are a challenge in controlling biofilms of pathogenic microorganisms, alternative measures to traditional methods for inactivating pathogens and biofilm formers bacteria are necessary. In this sense, lactic acid bacteria generate high levels of bacteriocin and are effective in inhibiting the biofilm of pathogenic bacteria, however, our study did not reveal this. We verified that Bifidobacterium animalis and Lactobacillus plantarum have an inhibitory action on Listeria monocytogenes, indicating that these lactic acid bacteria can be used to delay the formation of biofilms by Listeria on polystyrene surfaces, helping to control this pathogen in food industry. Keywords: control of biofilm, pathogenic bacteria, food industry, polystyrene surface, FTDs.